2018
DOI: 10.1148/rg.2018180090
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Tools for Department and Practice Communication and Branding in the Digital Age

Abstract: With nearly 70% of adults in the United States using at least one social media platform, a social media presence is increasingly important for departments and practices. Patients, prospective faculty and trainees, and referring physicians look to social media to find information about our organizations. The authors present a stepwise process for planning, executing, and evaluating an organizational social media strategy. This process begins with alignment with a strategic plan to set goals, identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Although social media has its benefits, curating an active presence on social media requires that accounts regularly post new content to remain relevant, which can be time-consuming (20). It is helpful to divide the efforts among multiple residents who share access to the account.…”
Section: Social Media Pearls and Pitfallsmentioning
confidence: 99%
“…Although social media has its benefits, curating an active presence on social media requires that accounts regularly post new content to remain relevant, which can be time-consuming (20). It is helpful to divide the efforts among multiple residents who share access to the account.…”
Section: Social Media Pearls and Pitfallsmentioning
confidence: 99%
“…Through the feedback process of socialization of continually deeper engagement, the identity becomes more refined until becoming a member of the community of practice [ 34 ]. In the case of our findings on digital identity, web-based metrics such as followers or increased web traffic were successful markers of socialization into the digital community and guided our participants to refine their digital identity by adhering to engagement strategies [ 35 ] and content that increased followings.…”
Section: Discussionmentioning
confidence: 99%
“…Research by the Google Shopper Science team showed that 71% of potential car buyers searched for information online before visiting a dealership. As consumers are substituting Internet-based searches for traditional searches [1], numerous studies have examined consumers' search behavior on the Internet [1,[4][5][6][7][8][9]. Furthermore, in today's online environment comprising numerous different types of information platforms, understanding information platforms and search behavior is important in planning a media strategy across a range of digital media [2,10].…”
Section: Introductionmentioning
confidence: 99%